The Learning Economy - Lundvall, Bengt-Åke; Johnson, Bjorn (Industry and Innovation, 1994)
Modern economies can be characterised as 'learning economies' in which knowledge is the crucial resource and learning is the most important process. Different kinds of learning and economically relevant types of knowledge can likewise be identified. It is argued that pure market economies, if such existed, would have severe problems in terms of learning and innovation. The 'learning economy' is a mixed economy in a fundamental sense.